Alcune idee di cibi, vini e banchetti letterari - Gino Ruozzi (DNA Di Nulla Academia, 2023)
Food and wine characterize Western culture and literature from the Bible and Homer’s poems to today. The essay proposes texts and authors from Greek and Latin to Italian literature from the Middle Ages to the twentieth century. The main examples of literary banquets are taken from Petronio, Giacomo Casanova, Carlo Emilio Gadda, Tomasi di Lampedusa, Goffredo Parise and Italo Calvino.